Identifying the best metrics to find the best quality clusters of genes from gene expression data - Choudhury, Joydhriti; Roshni, Tanzima Rahman; Chowdhury, Md. Tawhidul Islam; Rayon, Raihanoor Reza (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.